2022
DOI: 10.3390/cancers14102511
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analyses of a Novel Mouse Urothelial Carcinoma Model Reveal a Role of Tumor-Associated Macrophages in Response to Anti-PD-1 Therapy

Abstract: Approximately 80% of patients with advanced bladder cancer do not respond to immune checkpoint inhibitor (ICI) immunotherapy. Therefore, there is an urgent unmet need to develop clinically relevant preclinical models so that factors governing immunotherapy responses can be studied in immunocompetent mice. We developed a line of mouse triple knockout (TKO: Trp53, Pten, Rb1) urothelial carcinoma organoids transplanted into immunocompetent mice. These bladder tumors recapitulate the molecular phenotypes and heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…TKO tumours exhibited basal-like features and expressed, in contrast to lesions generated by implantation of MB49 cells, urothelial lineage markers. Treatment of subcutaneous TKO tumours with anti-PD-1 antibodies resulted in a mixed pattern of response reflecting immunotherapy responses observed in the clinics [ 33 ▪ ]. Tsuji et al generated orthotopic BC models using the cell lines MBT-2 and MB49 and female C3H/HeJ or C57BL/6J mice to assess the effects of the novel bacterial minicell-based integrin-targeted oncolytic agent VAX014.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…TKO tumours exhibited basal-like features and expressed, in contrast to lesions generated by implantation of MB49 cells, urothelial lineage markers. Treatment of subcutaneous TKO tumours with anti-PD-1 antibodies resulted in a mixed pattern of response reflecting immunotherapy responses observed in the clinics [ 33 ▪ ]. Tsuji et al generated orthotopic BC models using the cell lines MBT-2 and MB49 and female C3H/HeJ or C57BL/6J mice to assess the effects of the novel bacterial minicell-based integrin-targeted oncolytic agent VAX014.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…One preclinical study used a conditional knockout BC mouse model which showed a heterogeneous response to treatment with PD-1 inhibition. Responding tumors showed a higher number of intratumoral macrophages ( 86 ).…”
Section: The Tumor Immune Micro-environment In Bladder Cancermentioning
confidence: 99%